Risk factors and clinical features for pulmonary paragonimiasis-associated pneumothorax. - Yunhong Song; Jeongmin Lee; Wonchang Hahn; Yujeong Jang; Seungwon Na; Sang-Min Oh; Joo-Hee Hwang; Chang-Seop Lee; Yeong Hun Choe; Jeong-Hwan Hwang (Public Library of Science (PLoS), 2023)
Background Pulmonary paragonimiasis, a food-borne zoonotic helminthiasis, is a parasitic disease of the lung caused by infection with trematodes species of the genus Paragonimus. Although pneumothorax has been reported as occuring with paragonimiasis, to date no study has been performed concerning the clinical features and predictive risk factors for this condition. Methods This retrospective study, which aims to fill this gap, was conducted at Jeonbuk National University Hospital. All patients (aged ≥19 years) were diagnosed with paragonimiasis between May 2011 and December 2021. Medical records were reviewed and information concerning age, sex, vital signs, underlying diseases, clinical signs and symptoms, laboratory findings, radiologic findings, treatment, and clinical outcomes was collected. An odds ratio (OR) for the risk factors associated with pneumothorax was calculated using the binary logistic regression model. Results Among 179 consecutive patients diagnosed with pulmonary paragonimiasis, the postive rate of pneumothorax was 10.6% (19/179). Pneumothorax occurred mostly in the right lung (78.9%, 15/19), and intrapulmonary parenchymal lesions showed an ipsilateral relationship with pneumothorax (94.7%, 18/19). Fifteen patients (78.9%, 15/19) of pneumothorax associated with pulmonary paragonimiasis are accompanied by pleural effusion. Most of patients with pneumothorax (89.5%, 17/19) underwent chest tube insertion as a first treatment. Three patients (15.8%) showed relapses but in no case was a death recorded. Asthma (odds ratio [OR] 8.10, 95% confidence interval [CI] 1.43-45.91), chest pain (OR 8.15, 95% CI 2.70-24.58), and intrapulmonary lesions (OR 8.94, 95% CI 1.12-71.36) were independent risk factors for pulmonary paragonimiasis-associated pneumothorax. Conclusions Our findings suggest that clinicians should keep in mind the possibility of pneumothorax when approached by patients with pulmonary paragonimiasis complaining of chest pain, accompanied by intrapulmonary lesions or with asthma as an underlying disease.